ANOMALIES OF CORONARY ARTERIES. "ARTERY-COLLAR" - E. A. Ulbasheva; A. M. Namitokov; E. D. Kosmacheva (Инновационная медицина Кубани)
Anomalies of coronary arteries are very diverse. Due to angiography evolution, possibilities for their detection became more frequent, and it always attract attention of experts. In the present article, we describe a clinical case with a rare and insufficiently explored anomaly – presence of the single coronary artery.